Significant impacts on Egyptian legal system caused by Egyptian investment legislation - Elfakharani, Ashraf M. A. (Pak Publishing Group, 2016)
The Egyptian government and its legislators have been putting forth legislative amendments to its domestic laws that are controversial in relation to investment, tenders, bids, and investment guarantee as top priority.On one hand, they are doing this in order to encourage and reassure the foreign investors in Egypt, and on the other hand, they are likely facing psychological fears of international massive litigations.However, these legislative investment amendments could threaten and undermine the stability of inherited Egyptian jurisdiction systems and integrity. These amendments include providing avenues of escape of corruption and financial crimes through the reconciliations with the foreign investors who have been damaging the Egyptian economy and its citizens’ livelihoods.As the role, size, and impact of foreign investment grow worldwide. The mechanisms holding such entities accountable are actively diminishing. Unfortunately, the legal framework of foreign investment is aggressively shrinking the state’s role in regulating these foreign investment enterprises in Egypt, while challenging the very sovereignty and jurisdiction of the Egyptian court system to investigate allegations of violations committed by foreign investors.In effect, this results in absolute impunity by foreign investors in Egypt. Moreover, this trend of more legal privileges and the loose accountability to the foreign investors create a negative impact on Egyptian public interests and then on the Egyptian legal system as well as on the Egyptian Constitution.The aim of this paper, therefore, is to highlight the lawful deficiencies of the amended investment laws as well as its patterns trespass to the Egyptian Constitution. In addition, this paper brings out the implications of these violations on the inherited Egyptian legal system.